DESIGN "SANGRAI" TOOL FOR COFFE WITH STIRER FIN - Waluyo, Djoko Adi; Pramana, Yanatra Budi (Tibuana, 2019)
Coffe is one of the results of the commodity plantation that has a fairly high economic value among other crops and plays an important role as a source of foreign exchange, to create a taste of coffee and sold on the market, the important things are the selection of coffee beans and roasting processes. The tools currently existing are still roasted manually and semi-automatic. This research aims to design the tool automatic coffee roast system, analysis the feasibility roasted include capacity analysis.